Hepatitis C virus core antigen as a possible alternative for evaluation of treatment effectiveness after treatment with direct-acting antivirals. Issue 4 (2nd October 2019) - Łucejko, M; Tomasiewicz, K; Olczak, A; Tudrujek-Zdunek, M; Halota, W; Jelski, W; Donica, H; Krintus, M; Mroczko, B; Flisiak, R
ABSTRACT: Background : Chronic hepatitis C is a major public health problem around the world. In monitoring treatment efficacy, although costly and labour-intensive methods of molecular biology are often used, much cheaper and technically easier serological methods evaluating the concentration of HCV core antigen in serum are available. We evaluated HCVcAg quantification as a possible assessment of the treatment efficacy instead of HCV RNA quantification. Methods : We collected 514 serum samples from treated HCV infected patients. Quantitative evaluation of HCV RNA and HCVcAg was carried out before treatment, at the end of treatment, and at least 12 weeks following treatment termination. HCV RNA was determined by automated assay (Roche COBAS) and HCVcAg quantitation with ARCHITECT ci8200 analyser. Results : There was a significant correlation between HCVcAg and HCV RNA concentrations at baseline and follow-up visits, but not at the end of treatment. Among samples collected before the treatment, at the end of treatment and follow-up visit, concordance of HCV RNA and HCVcAg reached level of 98.1%, 98.9% and 98.7%, respectively. Diagnostic sensitivity, specificity, positive and negative predictive values of HCVcAg detection were >97%. Conclusions : HCVcAg measurement could be an alternative for determining HCV treatment efficacy after chemotherapy and could be an option in the diagnosis of HCV infection.